Respon Unsur Hara Nitrogen Dan Besi Terhadap Sifat Fisiologis Dan Pertumbuhan Tanaman Terong (Solanum Melongena L.) - Prakoso, Tangguh; Alpandari, Heny (Jurnal Agroekoteknologi, 2024)
Eggplant (Solanum melongena L.) is a type of tropical plant which is included in the vegetable horticulture group where it is widely cultivated on land and in the yard. The high nutritional content of eggplant makes one of the reasons this commodity is in great demand by the public. So to get optimal results it is necessary to have a nutrient that must be met in the growth process. The presence of sufficient nutrients in the soil is one of the important factors in supporting plants to complete their life cycle, such as growing and producing optimally. Therefore, fertilization is an important activity in order to increase the presence of nutrients to avoid nutrient deficiencies that can have a negative impact on the resulting production, one of which is a decrease in production quality. Based on data from research results, nitrogen nutrients play a very important role in growth, and at the same time is a limiting element for eggplant growth, this is evidenced by the low growth indicators obtained in treatments that are not given nitrogen elements such as leaf growth, chlorophyll and dry weight produced.